Impact of Pancreatic Cyst Fluid CEA Levels on the Classification of Pancreatic Cysts Using the Papanicolaou Society of Cytology Terminology System for Pancreaticobiliary Cytology. Issue 2 (February 2017) - Ajaj Saieg, Mauro; Munson, Valerie; Colletti, Shanna; Nassar, Aziza
Abstract : Background: The new proposed classification for pancreaticobiliary cytology has advocated the use of carcinoembryonic antigen (CEA) analysis of cyst fluid as an ancillary diagnostic tool for the determination of mucinous neoplasms in pancreatic cyst aspirates. We aimed to investigate the effect of CEA cyst fluid analysis on cases primarily called negative or nondiagnostic and on the sensitivity and specificity of the method. Methods: We retrospectively identified and collected all pancreatic cyst aspirates from 2010 to 2014 at Mayo Clinic, Jacksonville, Florida, along with available corresponding surgical diagnoses. Cases primarily classified as nondiagnostic or negative but that had a cyst CEA level of 192 ng mL −1 or higher were reclassified as mucinous neoplasms. Cytohistologic correlation was assessed whenever possible. Results: We retrieved pancreatic cyst aspirates from 255 patients who had a corresponding CEA level measurement. Median patient age was 70 years (range, 25–100 years). Among all samples, 129 (50.6%) had been classified as negative and 42 (16.4%) as nondiagnostic. Applying the new criteria, the number of samples previously classified as negative and nondiagnostic decreased considerably, with a statistically significant difference among negative cases. Fifty‐four cases (21.2%) had an available corresponding surgical diagnosis, and complete agreement was achieved in 95.4% of the cases. Use of the new cutoff for CEA levels increased the sensitivity and negative predictive value, compared with the original diagnoses. Conclusions: The incorporation of the new proposed terminology and CEA fluid analysis has significantly decreased the number of samples primarily classified as negative and nondiagnostic, along with improved test characteristics. Diagn. Cytopathol. 2017;45:101–106. © 2016 Wiley Periodicals, Inc.